2008
DOI: 10.1037/a0013197
|View full text |Cite
|
Sign up to set email alerts
|

Embryo donation families: A follow-up in middle childhood.

Abstract: Couples who conceive using donated embryos rear a child to whom they are genetically unrelated. It has been suggested that this may have negative consequences for parenting and child development. Findings are presented of the second phase of an exploratory study of families with a child conceived through embryo donation. Seventeen embryo donation families with a 5-9 year old child were compared with 24 adoptive families and 28 in vitro fertilisation families. The quality of the mother's parenting, and the chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
2
17
0
1
Order By: Relevance
“…A similar pattern was found for egg donation families in the United Kingdom (Golombok, Murray, Brinsden, & Abdalla, 1999; and in Finland (Söderström-Anttila, Sajaniemi, Tiitinen, & Hovatta, 1998). With respect to embryo donation, found that only 9% of parents of preschool children born through embryo donation had begun to talk to their children about the children's biological origins, rising to only 18% by middle childhood (MacCallum & Keeley, 2008). This was in stark contrast to the comparison group of adoptive parents, all of whom had disclosed the adoption to their children (MacCallum & Keeley, 2012).…”
Section: Rates Of Disclosure In Donor-conceived Familiesmentioning
confidence: 58%
See 2 more Smart Citations
“…A similar pattern was found for egg donation families in the United Kingdom (Golombok, Murray, Brinsden, & Abdalla, 1999; and in Finland (Söderström-Anttila, Sajaniemi, Tiitinen, & Hovatta, 1998). With respect to embryo donation, found that only 9% of parents of preschool children born through embryo donation had begun to talk to their children about the children's biological origins, rising to only 18% by middle childhood (MacCallum & Keeley, 2008). This was in stark contrast to the comparison group of adoptive parents, all of whom had disclosed the adoption to their children (MacCallum & Keeley, 2012).…”
Section: Rates Of Disclosure In Donor-conceived Familiesmentioning
confidence: 58%
“…In the only study of parenting and child development in families formed through embryo donation, families were found to be functioning well when the children were of preschool age (MacCallum, Golombok, & Brinsden, 2007) and when followed up in middle childhood (MacCallum & Keeley, 2008). The parents differed from comparison groups of adoptive and IVF parents only in terms of greater emotional overinvolvement with the children.…”
Section: Family Functioning In Nondisclosing Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger proportion (45%) thought that the donor should be anonymous to the recipient, and 47% thought that the recipient should be anonymous to the donor. A British study showed that nearly half of the mothers of children born after embryo donation were not going to tell their children about this (28). Many studies suggest that parents of children being conceived through various types of donations would rather not want that the child knew about the donation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence on the psychological development of embryo donation children has found that they show no problems during the early and middle childhood years, suggesting that the current system is not having adverse effects (MacCallum and Keeley, 2008). However, from an ethical analysis, the three reasons discussed seem inadequate to support the status quo, and suggest that social factors should have more of a role to play in embryo donation, as they do in adoption, albeit in a proportional manner.…”
Section: Parenting Selection Criteria For Embryo Donation Compared Withmentioning
confidence: 99%